2012
DOI: 10.3111/13696998.2012.667465
|View full text |Cite
|
Sign up to set email alerts
|

The threshold rate of oral atypical anti-psychotic adherence at which paliperidone palmitate is cost saving

Abstract: Although uptake of LAIs in the US has not been as rapid as elsewhere, many thought leaders emphasize their importance in optimizing outcomes in patients with adherence problems. The findings of this analysis support the cost-effectiveness of paliperidone palmitate in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…A decision-analytic model of paliperidone palmitate versus atypical oral antipsychotics showed paliperidone palmitate had lower total medical costs and greater effectiveness (i.e., dominant decision) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A decision-analytic model of paliperidone palmitate versus atypical oral antipsychotics showed paliperidone palmitate had lower total medical costs and greater effectiveness (i.e., dominant decision) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In a study population of previously incarcerated patients, the Paliperidone Palmitate Research in Demonstrating Effectiveness (PRIDE) trial reported a significant delay in treatment failure among those randomly assigned to PP, relative to those assigned to OAT [ 23 ]. Additionally, in a study conducted from the US healthcare payer perspective, PP was shown to be more cost-effective relative to OAT; specifically, PP patients had fewer mean annual days of relapse (8.7 days vs 17.8 days) and lower mean annual costs ($20,995 vs $22,481) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Edwards et al 35 investigated the threshold at which PP1M is more cost efficient than OAAs, and reported that PP1M patients saved $1486 in healthcare costs compared to patients with schizophrenia treated with OAAs. Furthermore, Pennington and McCrone 36 reported that patients with schizophrenia can experience excess relapse costs of $6033-$32,753, attributable to hospitalization.…”
Section: Discussionmentioning
confidence: 99%